2005
DOI: 10.1002/ajmg.b.30149
|View full text |Cite
|
Sign up to set email alerts
|

A family study of early-onset obsessive-compulsive disorder

Abstract: Results from family studies have suggested that obsessive-compulsive disorder (OCD) is a genetically heterogeneous disorder and have emphasized the importance of identifying valid subgroups of patients. The current study focused on early-onset OCD probands and examined the recurrence risks of OCD and tics among first-degree family members. One hundred six children and adolescents with OCD were recruited from a specialty clinic for OCD and 44 control individuals without OCD were identified by random-digit diali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
13

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(150 citation statements)
references
References 36 publications
12
125
0
13
Order By: Relevance
“…Similar studies 7,8 conducted in juvenile cases of OCD reported even higher familial risks. A recent meta-analysis 9 of 6 adult and 5 pediatric OCD family studies reported odds ratios (ORs) for OCD of 4.7 (99% CI, 2.4-9.2) and 25.6 (99% CI, 9.3-70.6), respectively.…”
supporting
confidence: 63%
“…Similar studies 7,8 conducted in juvenile cases of OCD reported even higher familial risks. A recent meta-analysis 9 of 6 adult and 5 pediatric OCD family studies reported odds ratios (ORs) for OCD of 4.7 (99% CI, 2.4-9.2) and 25.6 (99% CI, 9.3-70.6), respectively.…”
supporting
confidence: 63%
“…Probands were included if OCD symptom onset occurred before age 18 [early onset appeared associated with familiality in some studies [e.g., Pauls et al, 1995;Nestadt et al, 2000b;do Rosario-Campos et al, 2005] but not all [Fyer et al, 2005;Grabe et al, 2006]]. Probands with schizophrenia, severe mental retardation, Tourette's disorder, or OCD which occurred exclusively in the context of depression (''secondary OCD'') were excluded.…”
Section: Sample Recruitment and Inclusionmentioning
confidence: 99%
“…OCD itself is a familial [Pauls et al, 1995;Nestadt et al, 2000b;Fyer et al, 2005;do Rosario-Campos et al, 2005;Hanna et al, 2005b;Grabe et al, 2006] and heritable condition [Inouye, 1965;Carey and Gottesman, 1981;Nestadt et al, 2000a;Hudziak et al, 2004;van Grootheest et al, 2005]. However, molecular genetic studies of OCD are in their relative infancy, as are molecular genetic studies of GDs.…”
Section: Introductionmentioning
confidence: 99%
“…114 Although the etiology of OCD remains unknown, the results of twin studies, familial studies, and segregation analysis have provided evidence that OCD has a strong genetic component. [115][116][117][118][119] Some investigators have also found markers of oxidative stress in the brain tissues of patients with OCD. [120][121][122] Moreover, Kuloglu et al 120 showed significantly lower levels of vitamin E and C, and higher levels of malondialdehyde (MDA) in patients with OCD compared to controls, suggesting that OCD is linked to oxidative stress.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%